The impact of Hemodiafiltration with endogenous reinfusion (HFR) on micronutrient status in patients undergoing maintenance hemodialysis: study protocol of a randomized controlled trial - Changhao Zhu; Lingling Ding; Naiying Lan; Fanzhou Zeng; Dan Ye; Hao Wang; Bo Yang (BMC Nephrology)
Abstract Background End-stage renal disease (ESRD) is associated with significant morbidity and mortality, with patients often experiencing micronutrient deficiencies due to dialysis treatments. Hemodiafiltration with Endogenous Reinfusion (HFR) is a novel dialysis modality that combines diffusion, convection, and adsorption mechanisms to remove uremic toxins while potentially preserving essential nutrients. This study aims to assess the impact of HFR on micronutrient levels and removal rates in patients undergoing maintenance hemodialysis (HD). Methods This is a single-center, open-label, randomized controlled trial. Adult patients on maintenance HD will be randomized to two treatment arms: Arm A (Hemodiafiltration (HDF) followed by HFR) and Arm B (HFR followed by HDF), with a two-week washout period between treatments. Blood samples will be collected pre- and post-treatment to measure trace elements, water-soluble vitamins, and fat-soluble vitamins. Statistical analyses will include paired t-tests and Wilcoxon signed-rank tests for within-group comparisons, and repeated measures ANOVA for between-group differences, adjusting for potential confounders. Discussion This study will evaluate whether HFR offers superior retention of micronutrients compared to traditional HDF therapies, which may contribute to improved clinical outcomes for ESRD patients. Findings could provide valuable insights into the role of HFR in optimizing nutritional status and reducing dialysis-related complications. The cross-over design minimizes patient variability, enhancing the reliability of comparisons between treatment modalities. Trial registration This trial is registered with the Chinese Clinical Trial Registry (ChiCTR2500096698).